Free Active Chlorine in Sodium Hypochlorite Solutions Admixed with Octenidine, SmearOFF, Chlorhexidine, and EDTA - Krishnan, Unni; Saji, Sreeja; Clarkson, Roger; Lalloo, Ratilal; Moule, Alex J. (Journal of endodontics, 2017)
The therapeutic effects of sodium hypochlorite (NaOCl) solutions are dependent on the levels of free available chlorine (FAC). Mixing these solutions with irrigants can result in significant reductions in FAC. Although the effect of some irrigants on FAC is known, the effect of other commonly used irrigants is not. Thus, the therapeutic ramifications of the concurrent use of these on the efficiency of NaOCl solutions is not known. Aliquots of 5.2% (w/v) NaOCl solutions were admixed in proportions of 90:10, 80:20, and 50:50 with the following irrigants: octenidine dihydrochloride (OCT); SmearOFF (Vista Dental Products, Racine, WI), 17% EDTA; and 0.2%, 2%, and 5% chlorhexidine (CHX) solutions. Changes in FAC were measured by iodometric titration. Statistical differences between means were determined using a post hoc Tukey analysis test after an analysis of variance. OCT appeared not to affect FAC and was significantly different than all other irrigants, except for 90:10 and 80:20 mixtures of low concentration (0.2%) CHX. CHX solutions showed a marked concentration- and mixture proportion–dependent detrimental effect on FAC. The reduction of FAC between different concentrations of CHX was statistically significant in 80:20 and 50:50 proportions, with 50:50 mixtures of 5% CHX having the greatest influence. Mixtures containing even small proportions of SmearOFF or EDTA exhibited significant losses in FAC. OCT has little effect on FAC and can be used concurrently with NaOCl solutions. Higher concentrations of CHX significantly affect FAC. Their combined use with NaOCl solutions should be avoided. EDTA and SmearOFF should not be mixed with NaOCl solutions. •Mixing irrigants with NaOCl solutions can affect FAC levels.•A reduction in FAC reduces the therapeutic effect of NaOCl solutions.•Octenidine has a minimal effect on FAC and can be used with sodium hypochlorite solutions.•Chlorhexidine showed a marked concentration-dependent reduction of FAC.•Even small amounts of SmearOFF or EDTA cause a significant loss of FAC.